(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aims to measure and analyze the impact of digital financial innovation on entrepreneurial financial performance through digital financial knowledge. The study community was represented by employees of Iraqi private banks, a sample of this community was selected, the sample size was (91) individuals, the questionnaire was adopted as a data collection tool, the method of modeling small squares (Partial Least Squares) was used in statistical analysis, using the (Smart-PLS) program, and after conducting the data analysis process and obtaining results, several conclusions were reached, including digital financial innovation has a positive moral impact on entrepreneurial financial performance. Based on the conclusions reached, a number of recommendations were formulated, most notably the need for banks to use the internet and mobile phone to provide banking services, as the use of these methods leads to customers receiving banking services in a timely manner and with minimal effort and cost.